EMPIRICAL RESEARCH ON ORGANIZATIONAL BEHAVIOUR IN EDUCATION AND MANAGEMENT FOR CAREER DEVELOPMENT - Gaur, Vidhu (International Journal of Psychosocial Rehabilitation, 2020)
Educational institutions are considered organizations, which are consciously and resolutely coordinated social units, composed of two or more people. Organizations work to implement their tasks and functions to achieve desired goals and objectives. The members of organizations are dedicated to carrying out their job functions, which are aimed at achieving a common goal or set of goals. The main goal of this research work is to study organizational behaviour in education. The effective implementation of organizational behaviour in education contributes to the improvement of job performance, generates job satisfaction and leads to the achievement of desired goals and objectives. The main areas that have been considered are the nature and characteristics of organizational behaviour, the scope of organizational behaviour, the need for organizational behaviour in education, the contribution of educational fields to organizational behaviour, career development for the organizational behaviour and challenges organizational behaviour opportunities.